Angle of repose [compact disc, unabridged] - Stegner, Wallace, 1909-1993 (Blackstone Audio, 2010)
Confined to a wheelchair, a retired historian sets out to write his grandparents' remarkable story, chronicling their days spent carving civilization into the surface of America's western frontier.